(untitled) (Journal of Pharmaceutical Negative Results, 2023)
As a result of complete combustion of fuel, only carbon dioxide and water vapors are formed from it. In addition, nitrogen and residual oxygen are released into the atmosphere. Due to the lack of air, premature combustion of fuel occurs. It produces toxic gases carbon monoxide (CO), hydrocarbons (CN) and nitrogen oxides (NOx), which are dangerous for the environment and human life.